Manual de procedimientos para incentivar el ahorro energético en las empresas procesadoras de balsa del cantón Santo Domingo, año 2014 - Vergara Losano, Niller Omar (2015)
This manual developed, is aimed at solving the problems of high energy consumption in processing industries raft of Canton Santo Domingo and to promote the proper and orderly use of energy as they are resources that the company has in order contribute to economic growth and seeks to facilitate continuous improvement and control activities carried out in the business as it has developed processes and policies to follow for the correct use of energy. This project aims to develop a manual of procedures to encourage energy conservation and to meet these objectives must be: To implement policies tailored to the needs of the company where each department will be identified. Manual functions that contribute to the improvement and development of the company, in view of the responsibilities assigned to each employee and activities are only expressed verbally. Develop a manual of procedures that allows us to specify activities, define responsibilities, establish mechanisms for coordination, and avoid duplication of functions planning, organizing, directing and controlling the use of energy in order to achieve the objectives or goals of the organization so efficient and effective.